Internalization of the Values of Religious Moderation through Islamic Religious Education Learning in Secondary Schools - Lia Puji Astuti (Archipel: Journal of Indonesian Interdisciplinary Studies, 2026)
This study aims to describe the process of internalizing the values of religious moderation through Islamic Religious Education (ISE) learning in secondary schools. The background of the study is based on the complexity of student diversity and the need to strengthen balanced, tolerant, and inclusive religious attitudes during adolescence. The research approach used was qualitative with a descriptive design, which allows for in-depth exploration of learning practices and social dynamics in the school environment. The research subjects included Islamic Religious Education teachers, students, and school officials directly involved in the learning process. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies, while data analysis was carried out interactively through data reduction, data presentation, and drawing conclusions. The results show that internalization of religious moderation values occurs through reflective, dialogic, and contextual learning strategies, supported by teacher role models and an inclusive school culture. The synergy between formal learning and school social practices strengthens the meaning of values in a sustainable manner. Islamic Religious Education plays a strategic role in shaping students' religious attitudes that are adaptive to the reality of diversity and able to contribute to the creation of social harmony.